ANALYSIS OF EDGAR ALLAN POE’S THE TELLTALE HEART BASED ON SPEECH ACT THEORY - rostina nina; Asri Pratiwi Mulandari (IKIP Siliwangi, 2018)
Abstract This research is analyzing short story “The Tell-tale Heart” by Edgar Allan Poe based on speech act. Speech act consists of categories; representatives, directives, expressive, commissive, and declaratives. Researcher focused on representative speech act. This concerns fictional character of this story as a narrator who utters his belief toward situation he faced. A total of 128 utterances is analyzed and divided into categories of boasting, asserting, stating, informing, claiming, complaining, concluding, criticizing, reporting, describing, suggesting, swearing, and denying. Th result of this research has revealed that 39% representative speech act of reporting category is the most frequently used in the short story while the least including criticizing with 1%. This story is the perfect example of picturing representative speech act while not so many genres do so. By observing some points of utterances, reader will commence to understand the structure of speech act. Keywords:Speech Act, Short Story, The Tell Tale Heart.